Integrated analytical methodology to investigate bioactive compounds in Crocus sativus L. flowers. Issue 5 (26th February 2018) - Cusano, Erica; Consonni, Roberto; Petrakis, Eleftherios A.; Astraka, Konstantina; Cagliani, Laura R.; Polissiou, Moschos G.
Abstract: Introduction: The increasing interest on Crocus sativus L. over the last decades is caused by its potential employment as a source of biologically active molecules, endowed with antioxidant and nutraceutical properties. These molecules are present mainly in stigmas and tepals, these last generally considered as byproducts. Objective: To characterise bioactive compounds in stigmas, stamens, and tepals of Crocus sativus L. for quality, cross‐contamination of tissues or fraudulent addition, joining spectroscopic and chromatographic techniques. Methodology: Fourier transform infrared (FT‐IR) and Raman spectroscopies were initially employed, being very rapid in response; volatiles were more appropriately investigated by gas chromatography with mass spectrometry (GC‐MS), while finally nuclear magnetic resonance (NMR) and high‐performance liquid chromatography with a diode array detector (HPLC‐DAD) were adopted for a more thorough characterisation of secondary metabolites. NMR was also used to investigate the anthocyanins content in tepals upon acid extraction. Results: The results obtained highlighted the drying method as the dominant factor affecting the content of volatile constituents and contributing to the quality of saffron, while only slight differences were observed in the most abundant metabolites of stigmas, as well as in the anthocyanin content of tepals. In particular, for the first time, delphinidin and petunidin were detected by NMR in this latter tissue. Conclusion: The integrated analytical methodology here proposed, allowed to achieve a deeper level of compositional and structural details of secondary metabolites in Crocus sativus L. flowers. Abstract : The integrated analytical approach consisting of spectroscopic and chromatographic techniques is presented as a new tool to evaluate bioactive molecules in Crocus sativus L. flowers. The results confirmed the possible valorization of saffron byproducts (tepals) as a source of antioxidant molecules. In addition, possible markers for tissue cross‐contamination is suggested. Finally, the drying methods revealed to be crucial for quality attributes of saffron.